The Effect of Antinociceptive Flavonoid on Leea Indica Leaves for Orofacial Pain of Adult Zebra Fish (Danio Rerio) - Daya, Mei Putra; Saleh, Arman Yurisaldi; Astari, Riezky Valentina (Folia Medica Indonesiana, 2021)
Pain affects millions of people and is one of the most frequent complaints in the medical office. Pain involves various behavioral and emotional aspects. When it is persistent, it can become debilitating, impairing occupational performance, and producing negative impacts for the economy and public health costs. In general, commercial drugs can improve chronic pain patients' quality of life which can result in adverse reactions. Therefore, the search for new capsules as an opportunity remedy for ache is a challenge. Pain occurs due to stimuli from pain receptors called nociceptors. One pain known in the medical world is orofacial, defined as pain that occurs in soft and hard tissue in the head, face, and neck area. This study determined the antinociceptive effect of flavonoids isolated from the Leea Indica plant, on orofacial pain in zebrafish (Danio rerio) as a test model for behavior or locomotor activity. To study the orofacial pain of zebrafish induced with glutamate, this study was a true experiment. The parameter used was the number of times the fish crossed the line between the caudran from the glass petri dish during 0-5 minutes and 15-30 minutes. The Anova one-way test showed that there were differences in locomotors activity measured from 0-5 minutes and 15-30 minutes by giving flavonoids that could affect zebrafish locomotors activity or an increase in zebrafish locomotors activity. The antinociceptive effect of flavonoids was similar to tramadol. The flavonoids from Leea Indica had an antinociceptive effect on orofacial pain in adult zebrafish. The flavonoid dose of 2.5 mg/ml was a dose that had a significant difference in all treatment groups.